How safe is soy in infancy? Case report of thelarche in an infant - Tripathi, Parijat R.; Reddy, Rahul (International Journal of Contemporary Pediatrics, 2021)
Soy protein based formulas are commonly used in infant nutrition for various indications like lactose intolerance and cow’s milk protein allergy. There are concerns regarding phytoestrogen related and other side effects of these formulas. We are describing a case of possible soy formula induced thelarche in a 7 months infant. There was normalization of estradiol levels with some clinical improvement after stopping soy formula over a follow-up of 12 months duration. We suggest further studies to evaluate hormone levels in infants on soy formulas and to consider it only for appropriate clinical indication and age group.